2017
DOI: 10.1590/1809-2950/17015824032017
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of different levels of positive expiratory pressure on chest wall volumes in healthy children and patients with fibrosis

Abstract: Positive Expiratory Pressure (PEP) improves lung function, however, PEP-induced changes are not fully established. The aim of this study was to assess the acute effects of different PEP levels on chest wall volumes and the breathing pattern in children with Cystic Fibrosis (CF). Anthropometric data, lung function values, and respiratory muscle strength were collected. Chest wall volumes were assessed by Optoelectronic plethysmography at rest and during the use of different PEP levels (10 and 20 cm H2O), random… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
2
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 20 publications
1
2
0
2
Order By: Relevance
“…In a study involving patients with cystic fibrosis and healthy children during the use of two PEP intensities (10 and 20 cmH 2 O) for evaluating chest wall volume variation through OEP [ 4 ], the authors found similar results to the present study for EIV, which not only presented a significant increase during the PEP, but also while using the other two devices–except for the abdominal compartment during the IS-v–and also for the EEV during PEP. However, a significant reduction of EEV was observed in the chest wall, abdominal rib cage and abdominal compartment using IS-v.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…In a study involving patients with cystic fibrosis and healthy children during the use of two PEP intensities (10 and 20 cmH 2 O) for evaluating chest wall volume variation through OEP [ 4 ], the authors found similar results to the present study for EIV, which not only presented a significant increase during the PEP, but also while using the other two devices–except for the abdominal compartment during the IS-v–and also for the EEV during PEP. However, a significant reduction of EEV was observed in the chest wall, abdominal rib cage and abdominal compartment using IS-v.…”
Section: Discussionsupporting
confidence: 82%
“…Several situations in clinical practice favor subjects developing reduced lung volumes, characterizing a restrictive respiratory pattern [ 1 ]. Current evidence has already described that several patterns can be observed in the postoperative period of cardiac and abdominal surgeries [ 2 , 3 ], in patients with cystic fibrosis [ 4 ], obesity [ 5 ], Parkinson’s disease [ 6 ] and post-stroke [ 7 ]. The reduction in pulmonary volumes can promote pulmonary complications in the postoperative period and leads to worse quality of life for individuals, since simple tasks in daily life become impaired by lower ventilatory efficiency [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Sabe-se que a escolha das intervenções de FR é influenciada pela idade, gravidade clínica, avaliação e resposta terapêutica. No entanto, esta revisão não pode investigar a influência de todos esses fatores, considerando que apenas a idade e a gravidade clínica (função pulmonar) estiveram disponíveis em grande parte dos estudos 3,[12][13][14][15][16][17][18]22,23,25,28,29,31,32 . A escolha das intervenções parece ter sido influenciada pela faixa etária nos estudos selecionados, já que, conforme há o aumento da idade, ocorre a redução por terapias exclusivamente convencionais 14,18,19,22,23,25,[29][30][31][32] .…”
Section: Discussionunclassified
“…Recentemente, um estudo realizado 8 em diversos centros de referência da doença, no Brasil, evidenciou uma variabilidade na recomendação das intervenções de FR, embora as mais utilizadas foram os dispositivos de oscilação oral de alta frequência (Flutter ® , Shaker ® e Acapella ® ) e as de PEP, seguidos das intervenções baseadas em volume. Nos resultados desta pesquisa, as intervenções instrumentais ficaram em segundo lugar 3,12,13,[15][16][17]19,21,23,25,29,30 , sendo elas isoladas ou associadas às terapias, sobressaindo-se os dispositivos/máscara de PEP e o Flutter ® . Estas intervenções geram independência tanto aos pacientes quanto à família, sendo que sua escolha, no público jovem, pode acarretar uma melhor adesão ao tratamento 34,35 , visto que a FR faz parte, diariamente, da vida do indivíduo com FC 4 .…”
Section: Discussionunclassified
“…PEP therapy works by distending airways and preventing collapse of alveoli during expiration, and hence improving FRC. PEP therapy has been shown to improve FRC and tidal volume in healthy as well as children with cystic fibrosis (7). PEP therapy in form of expiratory positive airway pressure (EPAP) devices has also been found effective in obstructive sleep apnea, where it is proposed to work by splinting of airway, improved FRC and mild CO2 retention leading to improvement in respiratory drive (8,9).…”
Section: Physiological Basismentioning
confidence: 99%